2010
DOI: 10.1186/1756-3305-3-25
|View full text |Cite
|
Sign up to set email alerts
|

Heartworm (Dirofilaria immitis) infection in a leopard (Panthera pardus pardus) housed in a zoological park in north-eastern Italy

Abstract: Canine heartworm (cHW) disease is now recognised as potential cause of serious disease in cats and other felids, especially in endemic areas. In March 2009, a 23-years-old male African leopard (Panthera pardus pardus) housed in a zoological park located in the Province of Padova (Veneto Region), a cHW endemic area of the north-eastern Italy, died and was immediately necropsied. A cloth completely occluding the pyloric lumen was considered the presumptive cause of death. During necropsy, six nematodes (4 males … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2012
2012
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 16 publications
0
7
0
1
Order By: Relevance
“…In most cases, the infection was an accidental finding at necropsy and circulating microfilariae were never detected. However, microfilariae were recently recovered from a leopard (Panthera pardus pardus) in a highly endemic area of northern Italy (Mazzariol et al, 2010). In Serbia, one wild cat was found infected in 2009 in Serbia (Penezić et al, 2014), but no data of microfilaremia was reported.…”
Section: Dirofilaria Immitis and Dirofilaria Repensmentioning
confidence: 99%
“…In most cases, the infection was an accidental finding at necropsy and circulating microfilariae were never detected. However, microfilariae were recently recovered from a leopard (Panthera pardus pardus) in a highly endemic area of northern Italy (Mazzariol et al, 2010). In Serbia, one wild cat was found infected in 2009 in Serbia (Penezić et al, 2014), but no data of microfilaremia was reported.…”
Section: Dirofilaria Immitis and Dirofilaria Repensmentioning
confidence: 99%
“…In Tuscany too, epidemiologic studies observe the presence of adults of D. immitis between 6.06 and 7.1% of the red foxes studied (Magi et al, 2008 , 2009 ). For the first time, has been described the first diagnosis of mature heartworm infection and presence of microfilariae in an exotic felid ( Panthera pardus pardus ) in north-eastern Italy (Mazzariol et al, 2010 ). Furthermore, a case of D .…”
Section: Epidemiological Situation Of Animal Dirofilariasis In Europementioning
confidence: 99%
“…Nonetheless, the involvement of wild canids in spreading human dirofilarioses has never been properly investigated, although they could play a major epidemiological role, mainly because they are out of any preventative control strategies. Wild carnivores (Table 1) living in zoological gardens and free ranging ‘safari’ parks were diagnosed with D. immitis at necropsy (McCall et al, 2008; Penezić et al, 2014), however, microfilariae have exclusively been found in a leopard ( Panthera pardus pardus ) died in a zoological park in a highly endemic area of northern Italy (Mazzariol et al, 2010). In contrast, coyotes ( Canis latrans ), jackals ( Canis aureus ), wolves ( Canis lupus ) and foxes ( Vulpes vulpes ) living in their natural habitat have been found positive for D. immitis adults at necropsy (reviewed in Otranto et al, 2015b).…”
Section: Vector Borne Transmitted Nematodesmentioning
confidence: 99%